Time for mapping Cartographic temporalities - Hind, Sam (Manchester University Press, 2018)
"The digital era has brought about huge transformations in the map itself, which to date have been largely conceptualised in spatial terms. Novel objects, forms, processes and approaches have emerged and pose new, pressing questions about the temporality of digital maps and contemporary mapping practices: in spite of its implicit spatiality, digital mapping is strongly grounded in time. This collection brings time back into the map, taking up Doreen Massey's critical concern for 'ongoing stories' in the world; it asks how mapping enrols time into these narratives. Maps often seek to 'freeze' and 'fix' the world, looking to represent, document or capture dynamic phenomena. This collection examines how these processes are impacted by digital cartographic technologies that, arguably, have disrupted our understanding of time as much as they have provided coherence. The book consists of twelve chapters from experts in the field. Each addresses a different type of digital mapping practice and analyses it in relation to temporality. Cases discussed range from locative art projects, OpenStreetMap mapping parties, sensory mapping, Google Street View, to visual mapping, smart city dashboards and crisis mapping. Authors from different disciplinary positions consider how a temporal lens might focus attention on different aspects of digital mapping. This kaleidoscopic approach demonstrates a rich plethora of ways for understanding the temporal modes of digital mapping and the interdisciplinary background of the authors allows multiple positions to be developed and contrasted."